Analisis Kebutuhan Energi dan Rancangan Konservasi Energi di Politeknik Negeri Ketapang - Normansyah Normansyah; Yudi Chandra (Electrical Network Systems and Sources, 2022)
To anticipate the occurrence of power outages at the Ketapang State Polytechnic, it is supposed to immediately implement an energy management system as an opportunity for energy conservation. This system is designed based on a portrait of the current state of electricity use and forecasts of changes in patterns of electricity use in the future. This study aims to examine or study energy management by auditing the use of electrical energy and estimating the need for electrical energy at the Ketapang State Polytechnic institution during the period the next ten years, namely from 2013 to 2022 as well as drafting an energy conservation design that needs to be implemented as an effort to save electricity use at the Ketapang State Polytechnic so that it can reduce the cost of electrical energy. The research method used was a field survey conducted at the Campus The Ketapang State Polytechnic used data on the use of electrical energy in 2013. The research was carried out through four stages consisting of: the preliminary stage, the data collection stage, the data processing stage, and the analysis and conclusion stage. The results showed that: (1) the value of Energy Consumption Intensity (IKE) of 43 kWh/m2 which is much smaller than the standard IKE value for educational (office) buildings which is 240 kWh/m2 so there is no need to carry out a detailed energy audit, (2) there is a trend of increasing demand for electrical energy until 2022 around 10 %, (3) energy conservation design models that can be applied at the Ketapang State Polytechnic consist of: (1) light retrofit (adjustment/repair) of building/room construction, (2) utilizing the use of energy-saving technologies, (3) preparing and implementing SOPs for the use of facilities, and (4) conducting education and training for electric energy managers/users at the Ketapang State Polytechnic.